2017
DOI: 10.1186/s12876-017-0656-z
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of transarterial chemoembolization in patients with metastatic hepatocellular carcinoma: a single center experience

Abstract: BackgroundAs prognosis of patients with metastatic hepatocellular carcinoma (HCC) is mainly determined by intrahepatic HCC progression, local treatment with TACE may result in improved OS, although it is not recommended. The purpose of this study was to analyze retrospectively the efficacy of TACE and its impact on OS in patients with metastatic hepatocellular carcinoma (HCC).MethodsTwo hundred and fifteen patients with metastatic HCC who were treated at our Liver Center between 2003 and 2014 were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…Another study involving 240 patients with HCC found intrahepatic tumor status as a significant predictor of survival [20]; however, it was composed of a heterogeneous population (141 patients with EHM at diagnosis and 99 patients who developed EHM during follow-up) who underwent a variety of treatment. Another study from Germany analyzed 215 patients with metastatic HCC and reported that treatment with intrahepatic TACE (n = 42) and a combination of TACE and sorafenib (n = 23) were associated with improved survival [15]. However, the reference group comprised those without therapy (n = 102), and not those that received sorafenib (n = 48) as initial treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study involving 240 patients with HCC found intrahepatic tumor status as a significant predictor of survival [20]; however, it was composed of a heterogeneous population (141 patients with EHM at diagnosis and 99 patients who developed EHM during follow-up) who underwent a variety of treatment. Another study from Germany analyzed 215 patients with metastatic HCC and reported that treatment with intrahepatic TACE (n = 42) and a combination of TACE and sorafenib (n = 23) were associated with improved survival [15]. However, the reference group comprised those without therapy (n = 102), and not those that received sorafenib (n = 48) as initial treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The controllability of intrahepatic lesions was identified as an important prognostic factor for survival in HCC patients with EHM [11]. Hence, in real-life practice, some patients with HCC and EHM have been treated for intrahepatic HCC using locoregional treatments, usually transarterial chemoembolization (TACE) [1215], without robust evidence to support. Moreover, these data were derived from an era when sorafenib and other immunotherapic agents were not widely available.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular invasion or extrahepatic tumor spread lead to no curative treatment options available. Metastatic HCC (MHC) is mainly determined by progression of the underlying liver disease rather than by the extrahepatic metastases . In China and Africa patients who present with symptoms usually die within 4 months but longer survival is possible in western countries .…”
Section: Introductionmentioning
confidence: 99%
“…8 However, patients with HCC are often diagnosed in advanced stages, and even after complete HCC tumor resection or ablation, the carcinogenic tissue microenvironment in the remnant liver can give rise to recurrent de novo HCC tumors, which progress into incurable, advanced-stage disease in the majority of patients. 9 The recent alarming increase in the incidence of HCC in thalassemias, prompted us to overview the most common risk factors involved in the development of HCC, to briefly describe the frequency and the clinical and diagnostic characteristics, and to discuss the recommendations for HCC surveillance in high-risk patients with β-thalassemias. The preliminary data of the International Network of Clinicians for Endocrinopathies in Thalassemia and Adolescent Medicine (ICET-A) on HCC survey in thalassemia major (transfusion-dependent thalassemia:TDT) and intermedia patients (transfusion-dependent thalassemia: NTDT) are also presented.…”
mentioning
confidence: 99%